The Effects of Mandatory and Voluntary Regulatory Pressures on Firms’ Environmental Strategies: A Review and Recommendations for Future Research - Aragòn-Correa, J. Alberto; Marcus, Alfred A.; Vogel, David (Academy of Management Annals, 2020)
This article presents an in-depth review of scholarship on how mandatory and voluntary regulatory pressures on firms affect their environmental strategies and performance. Although mandatory regulation typically has a strong and positive influence on firms’ environmental performance, studies of the effects of voluntary pressures demonstrate that by themselves they are unlikely to bring about significant improvement in environmental outcomes. Accordingly, future research should focus on the complementary impacts of mandatory and voluntary programs on organizations’ environmental strategies and performance rather than analyzing their separate influence. Scholars should examine i) more than a single environmental pressure at a given time, ii) more than one response to the regulatory context, iii) the synergy between mandatory and voluntary pressures, iv) the impact of imperfect enforcement, and v) the political influence corporations exert on the mandatory and voluntary pressures that affect them. This essay argues that managers react to environmental regulations in different ways depending on how they understand the multiple pressures that they confront and their opportunities to influence the outcomes.